The effect of selected molecules influencing the detrimental host immune response on a course of rabies virus infection in a murine model. Issue 33 (2nd August 2019) - Smreczak, Marcin; Marzec, Anna; Orłowska, Anna; Trębas, Paweł; Reichert, Michał; Kycko, Anna; Koraka, Penelopa; Osterhaus, Ab; Żmudziński, Jan Franciszek
Highlights: TNF-α and MAPK inhibitors significantly extended mice survival SHBRV-18 infected. Studies on combination of both inhibitors, dose, route of administration are needed. TNF-α and MAPKs inhibitors may have the therapeutic potential in clinical rabies. Abstract: Rabies is invariably fatal, when post-exposure prophylaxis is administered after the onset of clinical symptoms. In many countries, rabies awareness is very low and the availability of post-exposure prophylaxis, as recommended by WHO guidelines, is very limited or non-existent, probably as a consequence of high cost. Therefore, new concepts for rabies therapy are needed. Innate immune mechanisms involving the production of pro-inflammatory cytokines and chemokines, activated after rabies infection, are thought to be involved in the neuropathogenesis of rabies. These mechanisms can contribute to a detrimental host response to the rabies virus (RABV) infection. The use of inhibitors of cytokines/chemokines are supposed to extend the survival of a sick individual. Inhibitors of TNF-α, IL-6 and MAPKs were used in RABV inoculated mice to define their influence on the survival time of rabid mice. The study demonstrated that all inhibitors extended mice survival, but at different rates. A log-rank test confirmed the statistically significant survival of mice treated with TNF-α (p = .0087) and MAPKs inhibitors (p = .0024). A delay in the time of onset of rabies was also recorded, in mice given TNF-α and MAPKs inhibitors. The highest virus load was found in the spinal cord and the lowest in the cortex, regardless of the experimental group. Significant TNF-α (p ≤ .0001) and IL-6 (p ≤ .0001) gene upregulation was observed in mice, as a consequence of RABV infection. Regarding MAPKs pathways, there was significant upregulation of the caspase 3 (p = .012, p = .0026) and Mcl-1 (p = .0348, p = .0153) genes, whereas significant downregulation of the cytochrome C (p ≤ .0001), Bcl2 (p = .0002, p = .0007) and JNK3 (p = .042) genes. Rabies pathogenesis is multifactorial, involving both virus and host influences on the course of the infection.